math

posted by .

solve the following:
ax + by = a-b
bx - ay = a+b
find the value of x and y

  • math -

    abx + b^2y = b(a-b)
    abx - a^2y = a(a+b)

    (b^2+a^2)y = -(a^2+b^2)
    y = -1
    similarly,
    x = 1

  • math -

    This is not perfect solution

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    use substitution to solve the linear system 3x-y=15 x+2y=-2 Solve for y in one formula, and then substitute that value for y in the other formula to solve for x. Once you find x, substitute that value into either formula to get the …
  2. algebra

    use substitution to solve the linear system 3x+2y=-5 4x-3y=16 help plz!!! Solve for y in one formula, and then substitute that value for y in the other formula to solve for x. Once you find x, substitute that value into either formula …
  3. Math

    Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 Please get me on the correct track for 3x -4y =8 x=4, y=1 for 6x - 2y =10 x= 2, y= 1 Solve one equation for x. 3x = 4y + 8 x = (4y + 8)/3 Insert that value …
  4. math

    Solve the following equation. x^2 + 28x = 0 x = 1 (smaller value) x = 2 (larger value)
  5. math

    Solve the following equation. 4m^2 = 2 − 7m m = 1 (smaller value) m = 2 (larger value)
  6. math

    Solve the following equation. ( x^2 + 8x + 7 = 0 x = 1 (smaller value) x = 2 (larger value)
  7. SAT Math

    Can I please get some help on these questions: 1. If , find the value of 2 square root of 17-x = 2x-10, find the value of x/4. 2. If absolute value of 3x+6 < 9, then which of the following is a possible value of x ?
  8. SAT math

    1. x>15-2x / -3 Solve the linear inequality. Write the solution in set builder notation. So, -3x>15-2x, x<-15..?
  9. math

    1.solve for p 3(p+q)=p A.q=-2/3p B.q=-3/2p C.p=-2/3q D.p=-3/2q 2. solve for b then find the value of b when a=3 4a=2b-7 A.-9/2 B.5/2 C.19/2 D.17 3. solve for r d=rt A.r=dt B.r=t/d C.d/t D.r=d-t 4. find the width of a rectangle with …
  10. Math

    Find the value of the following expression: (2^8 x 5^-5 x 19^0)^-2 x (5^-2/ 2^3)^4 x 2^28 Can someone show me the steps on how to solve this?

More Similar Questions